The causal relationship in law and nature: brief study on the legitimacy of imputation of the harmful result (Revista do Tribunal Regional Federal da 3ª Região, 2018)
The aim of this article is to analyze the way in which the law deals with cause and effect relationships, thus contrasting the notions of physical causality and legal causality. Thus, by differentiating between the types of causality, a better understanding of the imputation of a harmful result is possible, even when there is no naturalistic causal correlation.
Keywords: physical causality; legal causality; imputation; legitimacy